Editor's Choice – Infra-Renal Aortic Diameter and Cardiovascular Risk: Making Better Use of Abdominal Aortic Aneurysm Screening Outcomes. (July 2021) - Sidloff, David A.; Saratzis, Athanasios; Thompson, John; Katsogridakis, Emmanuel; Bown, Matt J.
Abstract : Objective: Aortic diameter (AD), used traditionally for abdominal aortic aneurysm (AAA) screening may have a role in assessing cardiovascular risk. Unfortunately, AD estimates for those without AAA are underutilised, whilst cardiovascular risk is sub-optimally managed in those with AAA. Our objective was to examine the association between AD measurements and future cardiovascular risk. Methods: Retrospective analysis of three databases of male participants screened for aortic aneurysm disease. Imaging and clinical data were obtained from three independent sources: 1) the Multi-centre Aneurysm Screening Study (MASS) trial ( n = 26 882 men); 2) the 2013/14 cohort of the English NHS AAA Screening Programme (NAAASP) ( n = 237 441 men) linked with NHS hospital admission and death registry data; and 3) the Framingham Heart Study (FHS) offspring cohort ( n = 649). Associations between maximal aortic diameter, as measured on ultrasound or computed tomography, and cardiovascular outcomes were examined. Results: Cardiovascular mortality in the MASS trial, was higher in men with AAA at 13 years of follow up, compared to those without (Hazard Ratio [HR] 2.22, 95% CI 1.97–2.50, p < .001). Contemporary risk of major adverse cardiovascular events in the NAAASP was highest in those with an AAA (HR 2.91, 95% CI 2.00–4.25), whilst, extremes of aortic diameter were associated with increased risk for cardiovascular events. Aortic diameter was an independent risk factor for cardiovascular events in the FHS dataset. Conclusion: Irrespective of the diagnosis of AAA, men attending for AAA screening who are found to have an abnormal aortic diameter are at high risk of future cardiovascular events. This currently unutilised data from AAA screening programmes has the potential to improve preventative management of cardiovascular risk.